What is known and not known about volunteer policing in the United States. (September 2016) - Dobrin, Adam; Wolf, Ross
Volunteer police have always been a part of policing, and currently field approximately 20% of the numbers of full-time paid officers in the United States. Given this long history and significant participation, it is surprising how little is known about this aspect of policing. This article reviews what is known about modern volunteer police in the United States, then explores what is not known. The implications for future research include a discussion of what researchers "need to know" and "should know" in order to have valuable evidence to guide evidence-based decision making for relevant stakeholders and policy-makers.